LONG-TERM OPERATIONAL MODEL OF AUTONOMOUS UNDERWATER VEHICLES (AUV) FOR MARITIME DEFENSE AND SECURITY - Tomy Ronaldi; Nizirwan Anwar (RADJA PUBLIKA, 2026)
This study aims to develop a long-term operational model for Autonomous Underwater Vehicles (AUVs) to enhance maritime defense and security. It focuses on optimizing AUV deployment strategies, improving endurance and navigation efficiency, and integrating advanced technologies to support autonomous maritime operations. The research employs a descriptive-analytical approach, utilizing literature reviews, technical simulations, and expert validation. It examines the integration of energy-efficient propulsion, AI-based navigation, and acoustic communication systems to enhance AUVs' long-term operational capabilities. The study reveals that the implementation of AI-driven navigation, high-capacity energy storage, and robust underwater communication significantly improves AUVs’ endurance and mission effectiveness. However, challenges such as high procurement costs, environmental constraints, and cybersecurity risks must be addressed to ensure sustainable operations. The findings highlight the importance of developing local AUV manufacturing capabilities and enhancing interoperability with existing maritime defense systems. This research contributes to the advancement of autonomous maritime defense by proposing a scalable and adaptive AUV operational model. It provides strategic recommendations for defense planners and policymakers to strengthen Indonesia’s maritime surveillance and security infrastructure.